The role of microclimate, vegetation variety and land use in the formation of humic substances - Mindari, W; Chakim, M.G.; Sasongko, P.E.; Aditya, H.F.; Karam, D.S.; Masri, I.N. (Malaysian Society of Soil Science, 2024)
Land use is significantly crucial in determining the supply of soil organic carbon (organic-C), including humic substances derived from plant litter composition. In this context, the lignin content of organic matter is strongly correlated with the formation of humic substances, providing benefits for human well-being. Microclimate is also thought to have a significant relationship in the formation of humic substances, where lower temperature decelerates decomposition. Therefore, this research aimed to investigate the role of microclimate and vegetation on the formation of humic substances. A total of six types of land use, including mixed crop, coffee plantation, and vegetable field, apple plantation, pine forests, and conservation forest were evaluated for temperature, forest humidity, type of vegetation, and organic-C content of plant litter. The results showed that temperature and humidity affected the levels of humic substances. Higher temperature was found to be correlated with lower organic-C content. The type of vegetation significantly affected the quality and quantity of plant litter, influencing organic-C content and humic substances. The use of coffee plantation land showed an increase in organicC content, which affected the formation of 1.85% humic acids, 6.90% fulvic acids, and 91.25% humin